Protocol for the comparison of remote versus face-to-face osteoarthritis management programs (COASTAL): A randomized implementation trial - Shiwen Yuan; Jocelyn L. Bowden; Jillian P. Eyles; Vicky Duong; Stephen Messier; Elena Losina; Jean Frederic Levesque; Andrew M. Briggs; Michelle M. Dowsey; Leticia Alle Deveza; Nicole M. Rankin; Christian J. Barton; et al. (Osteoarthritis and Cartilage Open)
Objective: To determine the comparative effectiveness of three evidence-informed approaches to delivering osteoarthritis (OA) care in real-world settings: face-to-face services, telehealth services or a mobile application (app). Design: COASTAL (ACTRN12624000996561) comprises two aims: the primary aim is a three-arm, non-inferiority, comparative-effectiveness, type I hybrid implementation RCT; and the secondary aim is a superiority trial to compare the three interventions separately to an untreated, non-randomized control group. We will recruit 1348 participants (primary aim:1011 interventions; secondary aim:1011 interventions, 337 controls) with knee OA referred to a NSW public Osteoarthritis Chronic Care Program (OACCP). Eligible participants who consent to OACCP participation will be randomized 1:1:1 to receive care through the face-to-face OACCP, a telehealth service, or the “OA Coach” app, over 6-months. All participants will receive a standardized needs assessment; OA education; collaboratively developed, personalized management plan with a focus on therapeutic exercise, physical activity, pain management, and weight-management, according to each arm's mode of delivery. People who have declined OACCP participation will be eligible for the control group. The primary outcome is change in average knee pain during walking at 6-months (11-point NRS). Secondary, implementation, and economic evaluation outcomes will be collected at 6 and 12-months.The protocol was co-developed with people with knee OA, clinicians delivering the services, and other stakeholders. Ethical approval granted by the Northern Sydney Local Health District (2024/ETH01461). Conclusion: The results of this trial will provide critical evidence to help people with OA, clinicians, service planners and policymakers choose between different modes of delivering care for knee OA.